The effect of digitalization on the sustainability of Malaysian SMEs - Anas, Abu Jaish; Murdipi, Rafiqa; Abdul Razak, Dzuljastri; Mohd Alwi, Norhayati (Management Academic Research Society, 2023)
In many developing countries SMEs are considered as one of the main contributors to their economic growth. Despite this achievement, SMEs across different sectors, face various challenges and issues, including those SMEs in Malaysia. Covid-19 pandemic is one of the most recent issues that particularly affect the business operations Malaysian SMEs. Due to the implementation of the Movement Control Order (MCO), Malaysian SMEs struggles in handling the situation which caused limited supplies, huge drop in sales, less cash flows, and restrictions on face-to-face dealings. Enormous number of Malaysian SMEs have discontinued their business operations and failed to survive during this critical juncture. The phenomena alarmed the concern over the sustainability issue of SMEs. Sustainability requires businesses especially SMEs to be more profitable and respond faster to market changes. SMEs' sustainability would be attained if their resources are more sufficient and flexible. In responding towards sustainability issues during the uncertain environment, many SMEs have adopted technological advances and digitalization. Although initiatives in adapting technology existed among the SMEs and have proven to be valuable in supporting SMEs competitiveness, many faced failures in successfully adapting it due to various challenges. Digitalizing SMEs activities are challenged by the need for large capital, lack of specific resources, lack of knowledge, insufficient funds, inadequate planning and technological incapability. This paper deliberates the importance of having dynamic resource capabilities in ensuring a successful adaptation of digitalization by SMEs. The discussion is extended on the need of dynamic capabilities in handling uncertain issues, which eventually determines their sustainability.